Digital Technology in SMEs Sustainability Practies: A Systematic Literature Review - Amalia Siti Khodijah; Neni Meidawati; Ataina Hudayati; Sri Sudiarti (The Indonesian Accounting Review, 2025)
The popularity of sustainability topics has increased, not only ini large companies, but also in small medium enterprises (SMEs). This study aims to analyze trends in publications related to digital technology implementation on SMEs sustainability practice. This research employs bibliometric analysis with a quantitative approach to identify the most used theory, variables, most influential journals and articles in this domain. The articles was extracted from the Scopus database. After applying a set of criteria, 62 articles were selected for this analysis. This systematic review demonstrates that research on digital technology in sustainable practices of SMEs is continuously evolving. This study reveals that the European continent leads in prominent publications on this subject. The Resource-Based View Theory is frequently employed to develop conceptual frameworks within this research area. Potential avenues for future research have been identified to provide recommendations for further studies. It highlights the need for adopting new theories, embracing qualitative methods and conducting cross-generational studies. This study enhances the utilization of technology in sustainable practices of SMEs, this paper highlights the need to adopt novel theories and recommends embracing experimental and longitudinal research methodologies, to uncover deeper insights into the implementation ofdigital technology in SMEs sustainable practices.